A psychologically-based taxonomy of misdirection - Kuhn, Gustav; Caffaratti, Hugo A.; Teszka, Robert; Rensink, Ronald A. (Frontiers in Psychology, 2014)
Magicians use misdirection to prevent you from realizing the methods used to create a magical effect, thereby allowing you to experience an apparently impossible event. Magicians have acquired much knowledge about misdirection, and have suggested several taxonomies of misdirection. These describe many of the fundamental principles in misdirection, focusing on how misdirection is achieved by magicians. In this article we review the strengths and weaknesses of past taxonomies, and argue that a more natural way of making sense of misdirection is to focus on the perceptual and cognitive mechanisms involved. Our psychologically-based taxonomy has three basic categories, corresponding to the types of psychological mechanisms affected: perception, memory, and reasoning. Each of these categories is then divided into subcategories based on the mechanisms that control these effects. This new taxonomy can help organize the magicians’ knowledge of misdirection in a meaningful way, and facilitate the dialogue between magicians and scientists.